BIOGEOCHEMICAL ANALYSIS IN RELATION TO WATER QUALITY OF WAWA DAM, RIZAL, PHILIPPINES - Hilario, Jacqueline E; Se, Erwin O; Garcia, Jett Edzen; Almonte, Jose Jacob; Almonte, Rafael Miguel (MATTER: International Journal of Science and Technology, 2017)
This paper investigates the biogeochemical components of Wawa Dam, to determine its viability for human consumption. Macro-invertebrates and geological structures were assessed in relation to water quality. Quantitative analysis on the physicochemical parameters, such as, pH, temperature, total dissolved solids, total suspended solids, biochemical oxygen demand, dissolved oxygen, nitrates and orthophosphates were done, to compare with the standard criteria set by the Department of Environmental and Natural Resources Administrative Order 90-34, in four consecutive months, covering rainy and dry seasons. Results showed that, Class Insecta with 30.91% were the most abundant macro-invertebrates, while, sedimentary rocks, dominated the geological structures with 69.10%. Total suspended solids and total dissolved solids, revealed significant concentrations (P<0.05) having low levels with average mean values of 33.25 mg L and 155 mg L, respectively, as compared with the standard criteria for Class A (drinking water with complete treatment). Biological oxygen demand, dissolved oxygen, nitrates and orthophosphates with average mean values of 9.5 mg L, 6.4 mg L, 11 mg L and 1.1 mg L, respectively, did not meet the standard criteria. Temperature and pH were within the range of standard level. Wawa Dam with the presence of inhabitants and other sources of pollution, the water quality is deteriorating, based on these observed parameters: nutrient concentrations were quite alarming; macro-invertebrates were threatened, due to a very high biological oxygen demand, and almost in the minimum level of dissolved oxygen. Total suspended solids and total dissolved solids were significant, because of their low concentrations.